2021
DOI: 10.1093/bib/bbab065
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ABPpred: identifying antibacterial peptides in protein sequences using bidirectional LSTM with word2vec

Abstract: The overuse of antibiotics has led to emergence of antimicrobial resistance, and as a result, antibacterial peptides (ABPs) are receiving significant attention as an alternative. Identification of effective ABPs in lab from natural sources is a cost-intensive and time-consuming process. Therefore, there is a need for the development of in silico models, which can identify novel ABPs in protein sequences for chemical synthesis and testing. In this study, we propose a deep learning classifier named Deep-ABPpred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The Deep-AmPEP30 online server applies a convolutional neural network (CNN) for AMP prediction [ 22 ], though the tool is restricted to working with short peptides up to 30 amino acids (aa) in length. The Deep-ABPpred online server adopts Bi-LSTM with word2vec [ 23 ], also for short (≤ 30 aa) peptides [ 24 ]. The Bi-LSTM model from Wang and co-workers is designed for even shorter peptides (≤ 20 aa) and specializes to predicting AMPs against Escherichia coli [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Deep-AmPEP30 online server applies a convolutional neural network (CNN) for AMP prediction [ 22 ], though the tool is restricted to working with short peptides up to 30 amino acids (aa) in length. The Deep-ABPpred online server adopts Bi-LSTM with word2vec [ 23 ], also for short (≤ 30 aa) peptides [ 24 ]. The Bi-LSTM model from Wang and co-workers is designed for even shorter peptides (≤ 20 aa) and specializes to predicting AMPs against Escherichia coli [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the development of artificial intelligence technology, the importance and advantage of deep learning (DL) methods in the field of bioinformatics have been well demonstrated [16][17][18][19][20][21]. Various DL methods have been utilized for therapeutic peptides prediction [22][23][24][25], such as Fang et al proposed a predictor based on DL combined with a character embedding layer for anti-fungal peptides identification [24], Li et al developed a dual-channel deep neural network (DNN) model for identifying variable-length antiviral peptides [25]. Compared with the traditional ML methods that need to extract or select features manually, the DL models can automatically learn the feature representation with limited peptide knowledge [26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, artificial intelligence-based (AI-based) methods are used to predict potential activities of peptides, and the results of the wet experiment indicated that this technology is reliable for drug research. Based on this purpose, AI-based methods are grouped into two categories. One is a classifier based on the binary model, such as ATSE, Deep-ABPpred, mAHTPred, and Antifp . Due to limited amount of data, most machine learning-based (ML-based) methods adopted a support vector machine (SVM) or random forest (RF) algorithm by the use of feature abstraction technologies such as the composition feature, position feature, physicochemical properties, and so forth.…”
Section: Introductionmentioning
confidence: 99%